Maroon calyxes - Sakimin, Siti Zaharah (University Putra Malaysia, 2012)
Roselle (Hibiscus sabdariffa) is a tropical fruit from the Hibiscus family. The fruit has unique calyxes of the deepest maroon colour. Many parts of Roselle including seeds, leaves, fruits and roots are used in various foods. Among them, the fleshy maroon calyxes are the most popular. Calyx of Roselle is rich with various nutrients (protein, carbohydrate, iron,calcium) and vitamins. Roselle is believed to have originated from West Africa and is considered unique because the calyx of the flowers is used to produce the drink. Maroon calyxes are used fresh for making juice, jam,jelly, syrup, wine, gelatin, pudding, cakes, ice cream and flavours and also dried and brewed into tea which is caffeine-free.